Investigating the role of articulatory organs and perceptual assimilation in infants' discrimination of native and non‐native fricative place contrasts. (6th January 2014) - Tyler, Michael D.; Best, Catherine T.; Goldstein, Louis M.; Antoniou, Mark
ABSTRACT: The perceptual assimilation model (PAM; Best, C. T. [1995]. A direct realist view of cross‐language speech perception. In W. Strange (Ed.), Speech perception and linguistic experience: Issues in cross‐language research (pp. 171–204). Baltimore, MD: York Press.) accounts for developmental patterns of speech contrast discrimination by proposing that infants shift from untuned phonetic perception at 6 months to natively tuned perceptual assimilation at 11–12 months, but the model does not predict initial discrimination differences among contrasts. To address that issue, we evaluated the Articulatory Organ Hypothesis, which posits that consonants produced using different articulatory organs are initially easier to discriminate than those produced with the same articulatory organ. We tested English‐learning 6‐ and 11‐month‐olds' discrimination of voiceless fricative place contrasts from Nuu‐Chah‐Nulth (non‐native) and English (native), with one within‐organ and one between‐organ contrast from each language. Both native and non‐native contrasts were discriminated across age, suggesting that articulatory‐organ differences do not influence perception of speech contrasts by young infants. The results highlight the fact that a decline in discrimination for non‐native contrasts does not always occur over age. © 2014 Wiley Periodicals, Inc . Dev Psychobiol 56: 210–227, 2014.